Adubação potássica em videiras jovens e em produção no Sul do Brasil - Ciotta, Marlise Nara (2014)
The application of potassium (K) and lime as a source of Calcium (Ca) and Magnesium (Mg) in soil may affect the growth and nutritional status of young plants of grapevines as well as grape production, must composition and distribution of forms of K in the soil. This study aimed to i) evaluate the growth and nutritional status of young grapevines submitted to the application of K lime in soil ii) evaluate how potassium fertilization affects the grape production, must composition and alterations of forms of K in soil, and iii) evaluate the potential of water in leaves as well as the nutritional status and must composition of grapevines grown with or without irrigation. Four studies were carried out. In study I, two experiments were performed in Campanha Gaucha (RS) in order to assess young plants. In the experiment 1, 0, 30 and 60 kg K2O ha-1were applied. In the experiment 2, 0, 60, 120, and 180 kg K2O ha-1were applied with application of dolomitic and calcitic lime. The K content in leaves, plant height, stem diameter and pruned material weight were evaluated. Studies II, III and IV were carried out for plants in production with the installation of three other experiments. One of the experiments was performed in Serra Catarinense (SC) with 0, 50, 100, 150 and 200 kg K2O ha-1 yr-1. The second experiment was in Campanha Gaucha with five levels of K in the soil. The K content in leaf, berries, grape yield components, and must composition were evaluated in both experiments. The third experiment was carried out in the region of Trento (Italy) with grapevines in production, with or without irrigation the soil, where the water potential of plants as well as the nutrient content in the leaf and berry of grapes were evaluated. In the experiment with young plants, soil potassium fertilization increased the K only in the 0-10 cm layer and influenced the content of K in the leaves in the first season; however, it did not influence the growth of cv. Chardonnay or Pinot Noir. For plants in production in Serra Catarinense there was an increase in the levels of exchangeable, non-exchangeable and total K in soil with the application of potassium fertilizer. The application of K in the soil increased the concentration of K in leaf and petioles of grapevines; however, it did not affect grape production or the must composition. In Campanha Gaucha, the increase of the content of exchangeable K in the soil increased the total K in the leaves in flowering, the K content in the berries and the pH of the must; however, it did not affect grape production. Although providing less negative water potential in grapevine leaves, irrigation did not affect nutritional status or the enological parameters of the berry, showing little interference in its nutrient content.